(untitled) (Research, Society and Development, 2021)
This paper regards the actions of social projects dedicated to helping people who were impacted by dam failures and mining disasters at Serra do Brigadeiro, in the State of Minas Gerais, Brazil. The team that coordinates one of these projects has reported persistent civil rights violations along with direct and veiled threats. Under those circumstances, these collectives highlight the struggles of the locals who coexist with the effects of aggressive mining activity.